Pengaruh Labelisasi Halal, Label BPOM Dan Religiusitas Terhadap Keputusan Pembelian Pada Mahasiswa FEB Universitas Muhammadiyah Metro - Pratama, Fadilah; Suwarto, Suwarto (Jurnal Manajemen DIVERSIFIKASI, 2021)
THE EFFECT OF HALAL LABELIZATION, BPOM LABELS AND RELIGIUSITY ON COSMETIC PURCHASE DECISIONS IN STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS MUHAMMADIYAH METRO UNIVERSITY of Fadillah Pratama M Npm.16610115 ABSTRAK Fadilah Pratama M NPM. 16610115 The Influence of Halal Labeling, BPOM Labels and Religiosity on Cosmetics Purchase Decisions for Students of the Faculty of Economics and Business, Muhammadiyah Metro Supervisory University (1) H. Suwarto, S.E, M.M (2) Sri Retnaning Rahayu, S.E M.M Currently, cosmetic products have become a primary need for women who are the main target of the cosmetics industry. In addition, along with the times, the cosmetics industry has also begun to penetrate the men's and children's markets. The potential for this domestic market includes the increasing number of young people or the millennial generation. This study aims to determine 1) To determine the effect of halal labeling on purchasing decisions. 2) To determine the effect of BPOM Labels on purchasing decisions 3) To determine the effect of Religiosity on purchasing decisions. 4) To determine the effect of Halal labeling, BPOM Labels and Religiosity together on purchasing decisions. This study uses a quantitative approach. The survey method was chosen as the primary data source. The survey method focuses on collecting data on respondents who have certain information, allowing researchers to solve problems. Data collection was carried out using a questionnaire or questionnaire instrument. . In this study, the population was students of FEB Muhammadiyah University of Metro Technique, taking the sample using accidental sampling with a total sample of 82 people. The data collection technique used a questionnaire with a Likert scale. The results showed that: 1) there is a positive effect of halal labeling on purchasing decisions. 2) there is a positive effect of BPOM Label on purchasing decisions 3) there is a positive influence of "Religiosity" on purchasing decisions. 4) There is a positive influence on Halal Labeling, BPOM Label and Religiosity together on purchasing decisions. Keywords: Halal Labeling, BPOM Label and Religiosity and purchasing decisions.